Characterizing private investments and implications for poverty reduction and natural resource management in Laos - Keovilignavong, Oulavanh; Suhardiman, Diana (Wiley, 2018)
We examine the patterns and characteristics of private investment in Laos, and how these evolve in relation to the Lao government's investment incentive policies in particular, and the wider State policies in general. Our goals are to: (1) systematically describe and analyze the patterns and characteristics of private investment in the country, and (2) analyze investment outcomes in terms of economic growth, poverty reduction and livelihoods. We argue that while private investments in the resource sector have contributed to economic growth, they have also negatively impacted local resources and communities. From a policy perspective, we highlight the need to examine the actual significance of policy incentives provided by the Lao government, especially with regard to its ability to direct investment decisions, in terms of both geography and sector.